ANALISA KANDUNGAN EKSTRAKTIF KAYU KELAPA (Cocus nucifera Linn) BERDASARKAN UMUR DAN LETAK KETINGGIAN PADA BATANG - Henni Aryati (Jurnal Hutan Tropis, 2011)
This study aims to determine the content of extractive substances based on age andlocation heights on the stem.  The introduction of the nature and chemical compositionof wood is one of the basic assessment of the use of wood.  By knowing the content of extractive substances based on age and height location on the trunk. Be expected coconut wood, forest products are expected information technology allows the oil industry serve as a nutrient such as sawn boards, cement board and furniture. Based on the function of extractive substances eksraktif divided into primary andsecondary extraction. Substance is primary extractive extractive substances dissolved  in cold water extraction and hot water, extractive content in this group are seen at the end.  Extractive dissolved in cold water extraction on the tree with the age of 30 years old ± 3.1% and the tree age of 40 years old  ± 1.87%.  Extraction using hot water extractive content in the tree with the age of 30 years ± extractive content on bigger tip to the treatment of other parts of the value of extractive content of 28.27%, while the 40 years old tree extractive content of 11.67%. The value of content in the primary extraction is caused by a function of extraction is used by plants for growth while other types of extraction is estimated as dissolved mineral, salts, sucrose, polysaccharides,  starch, gum, soluble carbohydrates, proteins and vitamins.  The big difference in the content of the primary extraction of water extraction due to cold and hot water at ambient conditions extractive was dissolved in cold water extractives that have low molecular weight and a bit of dye, while the hot water to an increase in temperature accelerates the reaction and all the soluble extractive in cold water will be dissolved in hot water extraction. The amount of extractive properties will provide a more durable high when thesesubstances are toxic extractive and will cause damage to the timber if the content ofextractives contained in wood is the favored extractive substances of insects.